The financial crisis in New Zealand: an inconvenient truth - Chiang, CKH; Prescott, S (MIT, 2010)
The financial crisis has been the topic of recent financial debate and the motivation behind initiatives to tighten the regulations governing the financial sector. In New Zealand the financial crisis reached its height in 2006. This paper traces the development of the financial sector in New Zealand from the early 1970’s through to the financial collapse of 2006-2009 and the aftermath of regulatory reviews, finger-pointing and corrective measures that dominated the last three years to the present day. The paper argues that the financial crisis is the product of an inconvenient truth that has been legitimised over the past century, encouraged poor corporate governance practices, and that the knee-jerk reaction to correcting the regulatory framework is too-little too-late.
Keywords: Financial crisis; New Zealand; Corporate governance